Student Engagement and Its Relation to Quality Work Design: An Action Research Study - Bowen, Elizabeth R. (My University, 2003)
The purpose of this study was to find out which instructional activities students find most engaging, and what design qualities, including technology, are included in those activities. A focus group of students provided input about the kinds of lessons they found engaging in the past. Local middle school teachers designed lessons using the design qualities in Philip Schlechty's WOW framework (2002). Students assessed their own level of engagement in those lessons, and observers took notes of lessons and interviewed pre-selected students. The research found that these middle school students were more authentically engaged when lessons were connected to a product (Product Focus), when they were given a choice (Choice), when they were given a chance to work with others (Affiliation) and to let others see the results of their work (Affirmation), when the work is real and meaningful (Authentic), and when technology is used in meaningful ways (Novelty and Variety). The results of the study were communicated to the learning community through meetings with teachers and administrators. These meetings supported using Schlechty's WOW Framework to design quality work to give to students.
Keywords: Instructional Activities; Student Engagement; Design Qualities